2020
DOI: 10.5770/cgj.23.384
|View full text |Cite
|
Sign up to set email alerts
|

Health-care Workforce Training to Effectively Support Family Caregivers of Seniors in Care

Abstract: Introduction Family caregivers (FCGs) play an integral, yet often invisible, role in the Canadian health-care system. As the population ages, their presence will become even more essential as they help balance demands on the system and enable community dwelling seniors to remain so for as long as possible. To preserve their own well-being and capacity to provide ongoing care, FCGs require support to the meet the challenges of their daily caregiving responsibilities. Supporting FCGs results in better care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…In most dementia care models the focus on the caregiver is limited largely to bolstering the caregiver with the goal of sustaining care for the person with dementia. The caregiver is viewed less often as a person with needs of their own or as a partner on the care team (43). More recently dementia care investigators have recommended that models specifically assess and address caregiver's support needs to better assist them in their caregiving role and to maintain their well-being.…”
Section: Current Models Of Dementia Care: Biopsychosocial and Social Ecological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most dementia care models the focus on the caregiver is limited largely to bolstering the caregiver with the goal of sustaining care for the person with dementia. The caregiver is viewed less often as a person with needs of their own or as a partner on the care team (43). More recently dementia care investigators have recommended that models specifically assess and address caregiver's support needs to better assist them in their caregiving role and to maintain their well-being.…”
Section: Current Models Of Dementia Care: Biopsychosocial and Social Ecological Considerationsmentioning
confidence: 99%
“…Family caregivers often report that their needs are often overlooked in medical settings. Fisher et al (43) reported on a symposium conducted in Canada to identify factors that affected care provision to family caregivers by healthcare professionals. A primary finding was that family Recommends medications and provides a referral to a behavioral health specialist for psychotherapy…”
Section: Integrating Relational Care Into Dementia Care: Team Training and Toolsmentioning
confidence: 99%
“…We recognised a lack of clear and evidence-based competencies that would serve the training of the healthcare providers to support FCGs (Charles, Brémault-Phillips, Parmar, Johnson, & Sacrey, 2017;Fisher et al, 2020;Holroyd-Leduc et al, 2017). To move from 'policy, recommendations, standards and strategies' to 'practice' we set out to identify the foundational competencies needed to train the health workforce to support FCGs.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…There were two main stages in the development of our Caregiver-Centred Care Competency project framework (see Figure 2). First, in 2018, we ascertained the areas of focus for health workforce education (Fisher et al, 2020). The following year ( 2019), we translated the areas of focus for education into competency domains and identified the indicators and used a four-phased Modified Delphi process to validate the indicators.…”
Section: Developing the Competencies For Health Workforce Education To Support Fcgsmentioning
confidence: 99%
See 1 more Smart Citation